2013
DOI: 10.1126/science.1234532
|View full text |Cite
|
Sign up to set email alerts
|

A Reconciled Estimate of Glacier Contributions to Sea Level Rise: 2003 to 2009

Abstract: A reconciled estimate of glacier contributions to sea level rise: 2003 to 2009Gardner, Alex S; Bolch, Tobias; et al Abstract: Glaciers distinct from the Greenland and Antarctic Ice Sheets are losing large amounts of water to the world's oceans. However, estimates of their contribution to sea level rise disagree. We provide a consensus estimate by standardizing existing, and creating new, mass-budget estimates from satellite gravimetry and altimetry and from local glaciological records. In many regions, local m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

101
1,278
12
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,168 publications
(1,394 citation statements)
references
References 33 publications
101
1,278
12
3
Order By: Relevance
“…This important water reserve is certain to be impacted by, and reflect changes in, the snowmelt regime of HMA, as the timing of precipitation has been shown to be an important factor in the response of glaciers to climate change (Maussion et al, 2014;Wang et al, 2017). While many regions have seen rapid glacier retreat (Bolch et al, 2012;Kääb et al, 2012Kääb et al, , 2015Scherler et al, 2011), there exist regions of glacier stability and even growth, such as the Karakoram (Hewitt, 2005;Gardelle et al, 2012) and Kunlun Shan (Gardner et al, 2013;Yao et al, 2012). Our results (see Fig.…”
Section: Hydrologic Implicationssupporting
confidence: 44%
See 1 more Smart Citation
“…This important water reserve is certain to be impacted by, and reflect changes in, the snowmelt regime of HMA, as the timing of precipitation has been shown to be an important factor in the response of glaciers to climate change (Maussion et al, 2014;Wang et al, 2017). While many regions have seen rapid glacier retreat (Bolch et al, 2012;Kääb et al, 2012Kääb et al, , 2015Scherler et al, 2011), there exist regions of glacier stability and even growth, such as the Karakoram (Hewitt, 2005;Gardelle et al, 2012) and Kunlun Shan (Gardner et al, 2013;Yao et al, 2012). Our results (see Fig.…”
Section: Hydrologic Implicationssupporting
confidence: 44%
“…1, inset). The interaction of these climatic regimes with the complex topography of HMA -particularly the vast elevation gradients -creates a diverse set of snowfall regimes (Cannon et al, 2014;Kääb et al, 2012;Immerzeel and Bierkens, 2012;Gardner et al, 2013;Kapnick et al, 2014;Barnett et al, 2005;Dahe et al, 2006;Takala et al, 2011;Cannon et al, 2017).…”
Section: Geographic Settingmentioning
confidence: 99%
“…Nearly all mountain glaciers have been melting rapidly in recent decades (Gardner and others, 2013; Zemp and others, 2015) and this has been documented, especially in High Mountain Asia (HMA hereafter), in surveys of the whole ( Li and others, 2008;Cogley, 2016) or large parts (Bolch and others, 2012;Yao and others, 2012) of the region as well as in basin-scale and single-glacier studies (Fujita and Nuimura, 2011;Wang and others, 2013;Yang and others, 2013). As reported in these earlier studies, most HMA glaciers showed obvious shrinkage (area loss) and thinning (implying mass loss) except in the west, for example in the Karakoram ( Gardelle and others, 2012) and western Kunlun (Neckel and others, 2014; Kääb and others, 2015; Ke and others, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some glacier parts are below sea level and, because of the ice/water density Table 2 Comparison of mass change estimates during common periods, in mm SLE year -1 and the 90% confidence interval, where given in the source (2002/2005-2013/2015) and adding the estimate for Greenland peripheral glaciers from Gardner et al (2013) difference, even cause a slight lowering of the sea level when replaced by water. Meltwater from glaciers on land may be held back in lakes, which form in over-deepened parts of glacier beds when becoming exposed.…”
Section: Synthesis and Discussionmentioning
confidence: 99%
“…The most recent global estimates of glacier mass changes include Jacob et al (2012) with 0.41 ± 0.08 mm SLE year -1 (2003-2010 time period) and Schrama et al (2014) with 0.45 ± 0.03 mm SLE year -1 (2003-2013) using the mascon-based approach, Chen et al (2013) with 0.54 ± 0.10 mm SLE year -1 (2005)(2006)(2007)(2008)(2009)(2010)(2011) and Yi et al (2015) with 0.58 ± 0.04 mm SLE year -1 (2005-2014) using the forward modeling-based method, and the four following studies which combined GRACE-based estimates with other datasets (e.g., altimetry, literature assessment, sea-level budget approach): Gardner et al (2013) with 0.60 ± 0.08 mm SLE year -1 (2003-2009), Dieng et al (2015) with 0.58 ± 0.1 mm SLE year -1 (2003-2013), Reager et al (2016), an update of Gardner et al (2013), with 0.53 ± 0.09 mm SLE year -1 (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) and Rietbroek et al (2016) with 0.38 ± 0.07 mm SLE year -1 (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014). See Fig.…”
Section: Glacier Mass Change From Spaceborne Gravity Observationsmentioning
confidence: 99%